Bluetooth application programming with the Java APIs - Thompson, Timothy J. (Timothy Joseph), 1976-; Kline, Paul J.; Kumar, C. Bala.; Kumar, C. Bala. (Amsterdam ; Boston : Morgan Kaufmann, 2008)
Adoption of Bluetooth wireless technology has become ubiquitous in the last few years. One of the biggest steps forward is the standardization of Java APIs for Bluetooth wireless technology (JABWT). The latest updates to this standard is explained in detail in this book. The JABWT standard, defined by the JSR-82 Java Specification Request, supports rapid development of Bluetooth applications that are portable, secure, and highly-usable. Wireless device manufacturers have responded overwhelmingly to the JABWT specification by implementing JABWT applications in mobile phones and other personal wireless communications products. "Bluetooth Application Programming Essentials: Programming with the Java APIs" explains in detail how to write Bluetooth applications using the Java APIs to exploit the power of both technologies. Written by the specification lead for JSR-82 and two other key participants in developing the standards of JABWT, this book provides the authoritative explanations and concrete examples needed to get started right away. This book provides embedded Java developers with to-the-point information on the APIs in the specification with detailed programmatic examples of the APIs in use. A NEW chapter on the Push Registry definition (a new feature in the 1.1 version of JSR-82) has been added. Finally, the new Essentials version of the book will update the remaining chapters to reflect changes in the latest Bluetooth spec (2.1) and the industry as a whole. As a bonus, this edition of the book offers over 200 pages of added content on the website. This "bonus material" includes complete source code from examples in the book, the javex.bluetooth code package, the java.obex code package, an enhanced set of "Example Applications", and a tutorial on "Implementing JABWT on a Device." These code-heavy sections are actually more effective in electonic format where the application can be easily downloaded. KEY FEATURES & BENEFITS * By focusing only on the essentials, this concise resource enables software and hardware vendors to quickly develop Bluetooth applications for mobile devices in an increasingly competitive market. * The updated material examines crucial programming areas (including RFCOMM, OBEX, device discovery, service discovery, and L2CAP), which allows developers to not only successfully design, but master and build Java APIs for Bluetooth Wireless Technology. * Includes a new and valuable chapter that delineates the pivotal Push Registry feature? a recent development that will help programmers avoid the common problem of connection collision. * By providing real-world issues and problems involved in implementing the Java APIs specification, the book allows developers to identify with the text and encourages repeated reference.
Ch 1: Introduction -- Ch 2: An Overview of JABWT -- Ch 3: High Level Architecture -- Ch 4: RFCOMM -- Ch 5: OBEX -- Ch 6: Device Discovery -- Ch 7: Service Discovery -- Ch 8: L2CAP -- Ch 9 (NEW): Bluetooth and the Push Registry.
C. Bala Kumar's name appeared first on t.p. of earlier ed.
Includes bibliographical references (p. [279]-281) and index.
Keywords: Bluetooth technology; Java (Computer program language).; Application program interfaces (Computer software); Wireless communication systems; Electronic books